Swallowing Kinematics in Male Patients with Total Laryngectomy - Gölaç, Hakan; Aydınlı, Fatma E.; Dumbak, Aydan B.; İncebay, Önal; Enver, Necati; Yapar, Dilek; Düzlü, Mehmet; Bulut, Elif G.; Süslü, Nilda S.; Yılmaz, Metin (The Laryngoscope, 2025)
Objective The present study aimed to investigate the symptomatic swallowing complaints in individuals with total laryngectomy (TL) and reveal how swallowing kinematics differs between those with and without symptomatic dysphagia complaints. Methods A total of 34 subjects with TL were included in the study. Swallowing kinematics of those with symptomatic swallowing complaints (Group 1) were compared to those without (Group 2). Kinematic parameters including pharyngeal transit duration (PTD), maximum pharyngeal constriction ratio (MPCR), upper esophageal sphincter opening ratio (UESOR), upper esophageal sphincter opening duration (UESOD), and bolus clearance ratio (BCR) were investigated from Videofluoroscopic Swallowing Study (VFSS) records via ImageJ software. Results Symptomatic swallowing complaints were determined in 47.1% of the subjects (n = 16). Difficulty while swallowing solid foods and pills, diminished pleasure of eating, food getting stuck in the throat, and increased level of stress during swallowing were among the major swallowing complaints in the present cohort. PTD, MPCR, and BCR parameters were significantly higher in subjects with symptomatic swallowing complaints than those without. Conclusion These preliminary findings indicate that almost half of individuals with TL may have symptomatic swallowing complaints. The underlying pathophysiology of this phenomenon may be the devianced kinematic parameters including PTD, MPCR, and BCR in this population. Therefore, it is recommended to include the kinematic measurements in the dysphagia evaluation protocol in individuals with TL, most notably in those with symptomatic swallowing complaints. Level of Evidence 3 Laryngoscope, 135:809–817, 2025 The current study aimed to investigate the general swallowing complaints in individuals with TL and to reveal how swallowing kinematics differs between those with and without symptomatic dysphagia complaints.